Characterization of ice recrystallization inhibition activity in the novel freeze-responsive protein Fr10 from freeze-tolerant wood frogs, Rana sylvatica. (August 2019) - Le Tri, Dung; Childers, Christine L.; Adam, Madeleine K.; Ben, Robert N.; Storey, Kenneth B.; Biggar, Kyle K.
Abstract: Fr10 is a secreted freeze-responsive protein found in the wood frog ( Rana sylvatica ). This protein has gained notable research attention for its highly dynamic expression in response to seasonal freezing stress, while its over-expression has been documented to enhance freeze tolerance in cold-susceptible cultured cells. This study further characterizes the properties of this novel protein with regards to thermal stability and ice recrystallization inhibition (i.e. IRI) activity. Thermal stability was assessed using differential scanning fluorimetry, with an experimental Tm value of 50.8 ± 0.1 °C. Potential IRI activity of Fr10 was evaluated using a recently developed nanoparticle-based colorimetric assay, where Fr10 displayed the ability to prevent freeze-induced aggregation of gold nanoparticles. Based upon this assay, Fr10 protein appeared to have a low level of IRI activity and it was therefore predicted that one of Fr10's biological functions may be to inhibit ice crystal growth via recrystallization. A SPLAT cooling assay was then employed to directly characterize the IRI properties of Fr10 and provide further insight into this hypothesis. In the presence of 30 μM of Fr10, a 40% reduction in the mean grain size of ice crystals relative to the control samples was observed, thus introducing the possibility of Fr10 to inhibit ice recrystallization. Collectively, the results from this study provide new insight into the potential of further exploring the potential of this vertebrate freeze-responsive protein in cryoprotection. Highlights: This study explores the function of a novel freeze-responsive protein called Fr10. Fr10 was found to be thermally stable up to approx. 50.8 °C. Physiological concentrations of Fr10 exhibited IRI activity. Observed IRI activity implied that Fr10 is an ice-binding protein.